THE IMPORTANCE OF PSYCHOLOGICAL TRAINING IN THE SPIRITUAL DEVELOPMENT OF STUDENTS - Munojatkxon Sodiqovna Valiyeva; Ismailov Nodirbek Nurali Ogli (Western European Studies, 2024)
This article discusses the essence of social psychological training and its role in human life.
Keywords: physiological training; learning motivation; interaction